Etude comparative des caractéristiques physico-chimiques et microbiologiques des différents laits (chamelle, chèvre, brebis, vache) - ELAACHI, MERIEM; KELOUCHE, HANANE (My University, 2018)
Milk is considered as complete and balanced food because of its high number of nutrients (proteins, fats, minerals, vitamins and lactose). However, in order to reveal the particularities characterizing the milk of four species (goat, cow, camel and sheep), we oriented hygienic analysis, physico-chemical and microbiological, by noticing the main properties singling out this product consumed in Algeria. On this purpose, eight samples of milk were taken from several parts of the country (Tiaret, Tissemsilt, Sidi-Belabbes, Ghardaïa, Mostagamen) they were analyzed at the microbiology laboratory of Mostaganem University ITA. This study includes a microbiological analysis of the main specific microorganisms and damaging pathogens. The analysis of technological parameters included measuring density, pH and acidity. In contrast to the nutritional analysis that has touched the lipid, protein, and mineral composition. The comparative study of the physicochemical characteristics of milk showed that sheep's milk is richer in fat (7,4%) dry matter (18,33%), Protein material (5.35%) than the milk of other species. Contamination levels were interpreted on the basis of the microbiological criteria defined by the interministerial decree of 24 January 1998. Our results reveal the total absence of pathogenic germs as well as the bacteria fecal contamination index (faecal coliforms) and the number of total germs is found to comply with Algerian standards. Finally, the present study confirms the interest of setting up a milking hygiene training for breeders in order to obtain a good quality microbiological milk.
Keywords: analyse microbiologique; caractéristiques physico-chimiques; laits; l’arrêté interministériel; qualité hygiénique.; microbiological analysis; physicochemical characteristics; milks; interministerial decree; hygienic quality.